1987
DOI: 10.1063/1.338502
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic attenuation in nickel and iron at 9.4 GHz

Abstract: Sound transmission experiments on single-crystal and polycrystalline nickel and iron samples 10–20 μm thick demonstrate an amplitude dependence on conductivity indicative of an electron damping effect. The samples form part of the common wall between two microwave cavities. Transverse sound waves were generated via magnetostriction with a static magnetic field perpendicular to the sample surface and perpendicular to the incident microwave magnetic field. Longitudinal sound waves were generated by direct electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…At the same time, it was shown experimentally that surface acoustic waves (SAWs) can propagate in a Ni film over the distance of several millimeters [41]. This absence of significant damping observed for the studied SAWs with frequencies not exceeding 500 MHz is very different from the results of Homer et al [50], who reported the decay length L dec ≈ 5.8 µm for the longitudinal wave with the frequency of 9.4 GHz in Ni. The reason for such a difference most probably lies in a drastic reduction of damping, which should happen when the frequency of the elastic wave changes from about 10 GHz to several hundreds of MHz.…”
Section: Magnetic Dynamics Excited By Longitudinal and Transverse Ela...contrasting
confidence: 74%
See 3 more Smart Citations
“…At the same time, it was shown experimentally that surface acoustic waves (SAWs) can propagate in a Ni film over the distance of several millimeters [41]. This absence of significant damping observed for the studied SAWs with frequencies not exceeding 500 MHz is very different from the results of Homer et al [50], who reported the decay length L dec ≈ 5.8 µm for the longitudinal wave with the frequency of 9.4 GHz in Ni. The reason for such a difference most probably lies in a drastic reduction of damping, which should happen when the frequency of the elastic wave changes from about 10 GHz to several hundreds of MHz.…”
Section: Magnetic Dynamics Excited By Longitudinal and Transverse Ela...contrasting
confidence: 74%
“…The reason for such a difference most probably lies in a drastic reduction of damping, which should happen when the frequency of the elastic wave changes from about 10 GHz to several hundreds of MHz. As for the damping of transverse elastic waves in Ni, our results show that the magnetic damping of elastic waves (L dec ≈ 19 µm) could be stronger than the damping of electronic origin (measured L dec ≈ 29 µm [50]) at wave frequencies around 10 GHz.…”
Section: Magnetic Dynamics Excited By Longitudinal and Transverse Ela...mentioning
confidence: 76%
See 2 more Smart Citations
“…Ultrasonic measurements are commonly performed between 1 and 20 MHz, but it is possible by special methods to go to 1 GHz and beyond. 61,62 The electrical wave forms are usually bursts of several cycles at the frequency of interest. The bursts should be short enough in time to discriminate multiple echoes.…”
mentioning
confidence: 99%